Macroeconomic performances and financial systems determinants of Malaysia housing price / Nor Faezah Abdullah Sani - Abdullah Sani, Nor Faezah (Faculty of Business and Management, 2015)
Over the past few years, the house price of Malaysia has experienced significant price expansion and thus became a worrying trend for lenders. The main purpose of this study is to analyze the macroeconomics and financial systems determinant of Malaysia housing price. This paper examines empirically whether the increasing trend in the base lending rate (BLR), consumer price index (CPI), gross domestic product (GDP) and Kuala Lumpur Composite Index (KLCI) effecting the Malaysia housing price Index (MHPI). The study explores the relationship between the house price and the independent variables for 16 years starting Q1 1999 to Q4 2014 using 64 secondary data of each variables. In the process of findings there are few types of analysis were tested using Eviews Version 7.0, such as simple and multiple linear regression analysis. The result indicates that there are not all predictors in this study are significantly related to house price, The result indicates that base lending rate is the only independent variables in this study that are not significantly related to house prices. The paper is useful for investors, speculators, policies makers and buyers to know which factors to account for in housing investment decision. This paper can also serve as a guide for the government in stabilizing the residential housing price in Malaysia.